2011
DOI: 10.1111/j.1360-0443.2011.03409.x
|View full text |Cite
|
Sign up to set email alerts
|

The ‘check effect’ reconsidered

Abstract: Aims The “check effect” refers to the use of disability payments to purchase illegal drugs or alcohol. This article describes subsequent research concerning three interrelated issues: the check effect, whether receipt of disability payments is associated with more overall substance use, and potential policy responses to misuse of disability payments for substances. Methods Review and synthesis of published articles. Results Increased substance use at the beginning of the month has been described in a varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 64 publications
2
47
0
Order By: Relevance
“…These findings support a growing body of evidence that drug use and drug-related harm increase following SA cheque issue (Rosen, 2011). For example, the results from our study are consistent with prior aggregate-level results compiled from Insite, a supervised injection facility in Vancouver, showing an immediate increase following monthly SA disbursement for both the total number of injections performed and rates of non-fatal overdose (Zlotorzynska et al, 2014).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These findings support a growing body of evidence that drug use and drug-related harm increase following SA cheque issue (Rosen, 2011). For example, the results from our study are consistent with prior aggregate-level results compiled from Insite, a supervised injection facility in Vancouver, showing an immediate increase following monthly SA disbursement for both the total number of injections performed and rates of non-fatal overdose (Zlotorzynska et al, 2014).…”
Section: Discussionsupporting
confidence: 84%
“…A recent review has pointed out that monthly SA disbursement schedule alters the timing of substance use rather than increase the overall level of use over an extended timeframe (Rosen, 2011). Intensified use immediately following SA receipt may be the cause of much of the drug-related harm identified by observational studies to date.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, receipt of social assistance has been temporally linked to increases in drug consumption, binge drug use, overdose and violence, with the odds of high intensity drug use being significantly higher in the days following social assistance payments (Dobkin & Puller, 2006; Li et al, 2007; Riddell & Riddell, 2006). However, there is no indication that receipt of social assistance increases overall drug use above unabated poverty (Rosen, 2011). Participation in drug dealing has been associated with elevated risks of overdose and frequent drug use in addition to violence, HIV infection, and incarceration (Curry & Latkin, 2003; Latkin, 2002; Semple et al, 2011; Small et al 2013; Werb et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It was unexpected that new SSA beneficiaries showed a tendency toward fewer days of alcohol intoxication after being awarded benefits, since several previous studies have found receipt of a disability benefit check at the beginning of each month to be associated with increased substance use (36,37). While treatment studies have failed to confirm a relationship between public support benefits and substance use (38), none to our knowledge have found a reduction in substance use.…”
Section: Discussionmentioning
confidence: 92%